2012
DOI: 10.5923/j.fph.20120201.09
|View full text |Cite
|
Sign up to set email alerts
|

Rice Cooking Quality and Physico-Chemical Characteristics: a Comparative Analysis of Selected Local and Newly Introduced Rice Varieties in Ebonyi State, Nigeria

Abstract: The Choice of rice varieties by farmers and consumers and the rate at which farmers in Ebonyi state go for new rice varieties at the expense of indigenous varieties have become a source of worry to scientists in Nigeria. We assessed the cooking quality and physico-chemical characteristics of 15 selected indigenous and five newly introduced hybrid rice varieties grown in Ebonyi State, Nigeria. Significant variation (P<0.05) was detected among the 20 rice varieties for all the traits evaluated. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 9 publications
5
18
0
Order By: Relevance
“…This could be attributed to their gelatinization temperature since gelatinization temperature contributes directly to the cooking time of rice. Water uptake ratio obtained for the rice varieties were comparable with the values reported by Oko and Ubi (2012) and Frei, Siddhuraju, and Becker (2003). FARO 61 had the highest of water uptake ratio value.…”
Section: Physical Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…This could be attributed to their gelatinization temperature since gelatinization temperature contributes directly to the cooking time of rice. Water uptake ratio obtained for the rice varieties were comparable with the values reported by Oko and Ubi (2012) and Frei, Siddhuraju, and Becker (2003). FARO 61 had the highest of water uptake ratio value.…”
Section: Physical Propertiessupporting
confidence: 85%
“…where WUR is water uptake ratio, WCR is the weight of cooked rice (g) and WUCR is the weight of uncooked rice (g). Similar method was reported by Oko and Ubi (2012).…”
Section: Water Uptake Ratio (Wur)supporting
confidence: 66%
“…The SLIW of a large percentage (88.89 %) of the domestic rice varieties were minimal (0.03-0.13 %). This result was similar to values IJFS October 2020 Volume 9 pages 319-331 reported by Yadav et al (2007) for gruel solid losses of 0.025-0.52 g. Oko et al (2012) also reported solids in cooking water of 0.01-0.95 g while Thomas et al (2013) reported gruel solid loss of 0.03-0.06 g. The minimal values obtained for SLIW showed that there is less tendency of the grains to cling together when cooked. The imported rice varieties had the highest VWA (26.00-27.67 ml) compared to a local rice (25.33 ml).…”
Section: Other Cooking Properties Of Domestic Rice Varietiessupporting
confidence: 90%
“…The minimum cooking time for all the rice varieties ranged from 15-43.33 minutes and the optimum cooking time ranged from 17-45.33 minutes. This is within the ranges reported by Thomas et al (2013) and Oko et al (2012). The extra-long and long grains cooked for a shorter time (17-38.67 minutes) compared to the medium grains, Kpurukpuru and Ghesua, that cooked for 40 and 45.33 minutes respectively which were also of intermediate and high amylose content respectively.…”
Section: Other Cooking Properties Of Domestic Rice Varietiessupporting
confidence: 89%
“…Amylose content is significantly affected by the various storage intervals and treatments. Rice varieties with amylose content of more than 25% absorb more water and have a fluffy texture after cooking (Oko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%